Pengembangan Kreativitas Anak Usia Dini melalui Pembelajaran Seni Tari Kreasi di KB Harapan Sambiwayang 1 - Priskila Winy Merlina; Utami Arsih (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to describe the process of developing early childhood creativity through learning the art of creative dance at KB Harapan Sambiwayang 1. Creativity development is an effort to improve children's ability to express themselves, explore movement, and develop creative and critical thinking. The research method used is qualitative descriptive with a subject of 15 children in one class. Data collection techniques include participant observation, interviews with educators, and documentation of the learning process. The research results show that the learning of creative dance focuses on the stages of movement exploration, motion improvisation, and the formation of simple movements is effective in stimulating wiraga, wirama, and wirasa. Educators act as facilitators who provide stimulation through music and daily themes related to the surrounding environment.